Examining factors impacting local food production and food security in St Vincent and the Grenadines (SVG) – a Small Island Developing State (SIDS) - Ausgustus, Eden (The University of the West Indies Cave Hill Campus, 2022)
Consistent access to safe and nutritious food among Small Island Developing States (SIDS) has been distorted by unemployment and poverty, leading to food insecurity. This is further compounded by developmental trajectories such as urbanisation and modernity which impact on previously vibrant agricultural systems towards decreasing agricultural production. In addition to economic challenges, geographic isolation and environmental issues such as natural disasters brought on by climate change as well as limited natural resources have led to an increased reliance on food imports. Recently, SIDS have been faced with another major challenge threatening food security - the COVID-19 pandemic and its sequelae impact or health and the economy. To control transmission rates, non-pharmaceutical interventions (NPIs) including curfews, closure of borders and institutions have been employed, deepening the vulnerability of small-scale food producers. To address the overall local food production and food security issues, an ecologic community back yard gardening initiative using organic practices has been identified as a point of intervention by evidence review and group model building sessions. Here we examine potential barriers to the intervention including the impact of the COVID-19 pandemic and the recent La Soufrière volcanic eruption on food production and food security in a community project in St. Vincent and the Grenadines. Data has been collected using a mixed method design through case studies and a quantitative cross-sectional survey. The case studies will be analysed within a thematic framework and associations will be tested through linear and logistic regressions.
Keywords: COVID-19; La Soufrière volcanic eruption; Food Security; Backyard Gardening